What's advertising content worth? Evidence from a consumer credit marketing field experiment - Marianne Bertrand; Dean S. Karlan; Sendhil Mullainathan; Eldar Shafir; Jonathan Zinman (Yale University, Economic Growth Center, 2008)
Firms spend billions of dollars each year advertising consumer products in order to influence demand. Much of these outlays are on the creative design of advertising content. Creative content often uses nuances of presentation and framing that have large effects on consumer decision making in laboratory studies. But there is little field evidence on the effect of advertising content as it compares in magnitude to the effect of price. We analyze a direct mail field experiment in South Africa implemented by a consumer lender that randomized creative content and loan price simultaneously. We find that content has significant effects on demand. There is also some evidence that the magnitude of content sensitivity is large relative to pricesensitivity. However, it was difficult to predict which particular types of content would significantly impact demand. This fits with a central premise of psychology context mattersand highlights the importance of testing the robustness of laboratory findings in the field.
Keywords: D01; M31; M37; C93; D12; D14; D21; D81; D91; O12; 330; economics of advertising; economics & psychology; behavioral economics; cues; microfinance